Driving factors and benefits of using mobile devices by students at a federal public university - Leite, Felipe Kopp; Pereira Junior, Errol Fernando Zepka (Brazilian Journal of Production Engineering, 2021)
This article aims to analyze how the driving factors influence the use of mobile devices by students and the causal relationship of this use with the benefits generated. For that, an instrument was built, which was applied to 100 students from the administration course of a Federal Public University. During the data analysis, an exploratory factor analysis was initially performed using the SPSS software, through which the referred instrument was validated. Then, through the data already collected, a confirmatory factor analysis was carried out by modeling structural equations formed by driving factors and their influence on the use of mobile devices and the relationship of this use with benefits generated from it through the software. Smart PLS. As a result, two hypotheses regarding the driving factors and the use of mobile devices were accepted. Regarding the causal relationship between use and perceived benefits, all four hypotheses were accepted through the model. Concluding from this that the Cognitive aspect and the Teacher’s Role influence students to use mobile devices in the classroom, being perceived from this the benefits of productivity, organization, autonomy and didactics.